Creating burdock polysaccharide-oleanolic acid-ursolic acid nanoparticles to deliver enhanced anti-inflammatory effects: fabrication, structural characterization and property evaluation - Shanshan Zhu; Zhichang Qiu; Xuguang Qiao; Geoffrey I.N. Waterhouse; Wenqing Zhu; Wenting Zhao; Qiuxia He; Zhenjia Zheng (Food Science and Human Wellness)
This study explored the potential of polysaccharides from Actium lappa (ALPs) as natural wall materials for producing ALP-based nanoparticles to deliver poorly water-soluble oleanolic acid (OA) and ursolic acid (UA). Encapsulating OA+UA with ALPs (ALP:OA+UA, 50:1; OA:UA, 1:1) changed the crystalline nature to a more amorphous state through hydrogen bonding and involving O–H/C–O/O–C–O groups. ALP-OA/UA nanoparticles had a particle size and zeta potential (in water) of 199.1 nm/–7.15 mV, with a narrow unimodal size distribution, and excellent pH, salt solution, temperature and storage stability. Compared with ALPs, ALP-OA/UA nanoparticles showed enhanced anti-inflammatory activity (especially at a dose of 100 μg/mL) in a CuSO4-induced zebrafish inflammation model via down-regulating the NF-κB signalling pathway and gene expression of associated transcription factors and cytokines (TNF-α, IL-1β and IL-8). Therefore, ALP-based nanoparticles are natural and anti-inflammatory carriers for hydrophobic bioactive molecules.